Other-constituency theories and firm governance: is the benefit corporation sufficient? - Jonsen, Richard Harvey (Journal of management, spirituality & religion, 2016)
Stakeholder theory creates a core conflict between managers in publicly held corporations and their boards of directors. Benefit corporation legislation recently adopted in 31 states attempts to address this conflict between shareholder primacy doctrine and stakeholder theory. While benefit corporation statutes offer improvement over traditional corporate structure for firms operating according to instrumental stakeholder theory, they do not fully support the ends of normative stakeholder theory or alternative normative other-constituency approaches, such as recently introduced common good models of the firm. Managers choosing to employ normative other-constituency approaches may choose to put benefit corporation regulations to use in the states where these tools are available, but they will continue to be faced with conflicts between benefit corporation structure/governance and applying normative other-constituency approaches on a day-to-day basis in their operations.